KOMUNIKASI ORGANISASI DALAM PENINGKATAN KINERJA GURU DI MADRASAH TSANAWIYAH (MTs) AL-MAIDAR PANDAN - Syafaruddin, Syafaruddin; Suharja, Suharja; Hamzah, Mhd. (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2021)
This paper aims to analyze organizational communication in improving teacher performance at MTs Al-Maidar Pandan. This study used a qualitative approach with field research methods through in-depth interviews and participant observation. The results showed that: First, the principal communicated with the teacher verbally (in the form of meetings, briefings and face to face); and non-verbal (in the form of observations of teacher expressions, gestures and digital communication via smartphones). Second, the principal displays exemplary behavior, skills development and teacher professionalism, as well as a high salary. Third, the head of madrasah held consultations for teachers who are members of MGPM, trained in the use of laptops, and coordinated among teachers as well as education personnel at MTs Al-Maidar Pandan.